A quantitative meta-analysis of organizational ownership and technical efficiency: non-linear influence by facility types and time for nonprofit and for-profit healthcare providers. (2nd April 2020) - Freeman, Amy; Nam-Speers, Jiwon; Tokac, Umit
ABSTRACT: This study seeks to determine if for-profit healthcare organizations are more technically efficient than nonprofit organizations. We attempted to answer two questions: Does the technical efficiency of hospitals and nursing homes vary depending on ownership type? If so, how does time moderate the relationship between ownership and technical efficiency? Our findings do not show that for-profit healthcare providers are universally more technically efficient than nonprofit healthcare facilities. However, for-profit nursing homes are more technically efficient than nonprofit facilities, while there was no difference between nonprofits and for-profits in hospitals. An examination of healthcare facilities reveals that nonprofit institutions have only recently become efficient, while for-profit organizations were more efficient in the past. In conclusion, institutional changes in the healthcare delivery system of the US developed differently, depending on organization's ownership and facility types. Theoretical and practical considerations were recommended as a policy tool in healthcare practices in terms of market and population for technical efficiency.